APLICAÇÃO DE UM PLANO DE CONTROLE NO PROJETO DE UM MEDIDOR DE FORMA BASEADO EM APQP - ENDRUWEIT, ANDREAS A. B.; SCHMIDT, AUDRIEN V.; HEPP, CARLOS A.; SANTOS, DANIEL L. D.; RIBEIRO, LUIS F. M. (Salão do Conhecimento, 2013)
Resumo